Health Education Isi Piringku Terhadap Perilaku Ibu dalam Pemenuhan Nutrisi Pada Anak Pra Sekolah (3-5 Tahun) Di RA Al-Fajar Kandat Kecamatan Kandat - Nurhasanah, Nurhasanah; Wahyuni, Candra (Universitas Nusantara PGRI Kediri, 2020)
Difficulty eating in children often occurs in pre-school children by> 20%. Factors that emphasize how to feed children, eating atmosphere and food variations and factors given to children, meal times and frequency of eating children. Problems with eating difficulties in children can be bad for children's growth and development. Children can enjoy undernourished food (Underweight) because the food needed is in small amounts so it does not meet their nutritional needs. The purpose of this study is to analyze Health Education